Perception Level of BSI Customers in Meulaboh Post Account Migration - Teungku Faathir Muhammad Akbar (Ridwan Institute, 2021)
Bank BSI is known as a banking company resulting from the merger of three sharia commercial banks (Mandiri sharia, BRI sharia, and BNI sharia). There is great hope from all Indonesian people, especially for those who are Muslim, so that this BSI bank becomes a bank that brings many blessings and benefits to many people in the field of financial management. From the information obtained that since the BSI bank was inaugurated and run, there have been several complaints experienced by BSI customers in Meulaboh. Each of these complaints certainly affects the customer's mindset or perception about the BSI bank. This perception is very important for BSI bank management to know, because it can be useful for resolving any existing customer complaints or problems. BSI bank management can use this perception as a benchmark for company performance in every dimension including customer knowledge, professionalism, access, popularity, facilities, legality, products. These dimensions will be used in this study as a tool to measure and describe the extent to which the perception level of BSI customers in Meulaboh is based on demographic factors (age and gender) and non-demographic factors (occupation and income) using quantitative descriptive analysis. There are 100 respondents (BSI customers) who live in Meulaboh as a sample to fill out the research questionnaire. The result of this study is that customer perceptions based on demographic and non-demographic factors range from the medium/neutral category to the very high category. Overall all parts of the perception obtained positive results. It can be concluded from the results of the perception obtained that the community still has confidence in the complaint because it can be resolved properly by the management of the BSI bank in Aceh, especially in the Meulaboh area